2022
DOI: 10.34067/kid.0000182022
|View full text |Cite
|
Sign up to set email alerts
|

Lived Experiences of Patients Receiving Hemodialysis during the COVID-19 Pandemic: A Qualitative Study from the Quebec Renal Network

Abstract: Background: Hemodialysis patients have faced unique challenges during the COVID-19 pandemic. They face high risk of death if infected, and have unavoidable exposure to others when they come to hospital three times weekly for their life-saving treatments. The objective of this study was to gain a better understanding of the scope and magnitude of the impacts of the pandemic on the lived experience of patients receiving in-center hemodialysis. Methods: We conducted semi-structured interviews with 22 patients wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 25 publications
(52 reference statements)
0
13
0
1
Order By: Relevance
“…During the months of May and June 2020, all-cause mortality was 26% higher than that during 2017-2019. The higher mortality during the early pandemic months is likely due to missed dialysis treatments [22][23][24][25][26]. Thus, the more modest increase in mortality in Veteran patients receiving maintenance hemodialysis in the VA is likely due to lack of disruption in the delivery and receipt of dialysis treatments which involve both patient and systemrelated factors.…”
Section: Discussionmentioning
confidence: 99%
“…During the months of May and June 2020, all-cause mortality was 26% higher than that during 2017-2019. The higher mortality during the early pandemic months is likely due to missed dialysis treatments [22][23][24][25][26]. Thus, the more modest increase in mortality in Veteran patients receiving maintenance hemodialysis in the VA is likely due to lack of disruption in the delivery and receipt of dialysis treatments which involve both patient and systemrelated factors.…”
Section: Discussionmentioning
confidence: 99%
“…Menariknya, pasien yang menjalani hemodialisis paling lama paling tidak terpengaruh oleh perubahan akibat pandemi. Pasien hemodialisis menunjukkan ketahanan yang luar biasa, dan mungkin lebih banyak waktu yang dihabiskan dalam hemodialisis meningkatkan ketahanan ini (Malo et al, 2022).…”
Section: Perilaku Kesehatanunclassified
“…Our study of hemodialysis patients also found that masks interfered with their communication with HCWs, since they were unable to see HCWs' facial expressions. 14 In a recent systematic review of studies looking at physician and patient communication during the COVID-19 pandemic, protective equipment as a barrier to verbal and nonverbal expression was the most important theme under the topic of reduced communication. 23 Masks could also prevent patients from visually recognizing their HCWs.…”
Section: Feeling Of Loneliness and Isolationmentioning
confidence: 99%
“…5,9 Since the beginning of the COVID-19 pandemic, HCWs, including dialysis staff, have been at risk of increased psychological stress and distress given their exposure to death, lack of appropriate equipment, moral injury, increased workload, and the risks of COVID-19 infection. 10,11 The objective of our study, which is part of a larger study documenting the impact of COVID-19 on hemodialysis clinics in Quebec, [12][13][14] was to gather HCWs' experiences and perspectives of providing care during the first wave of the COVID-19 pandemic. A better understanding of the scope and magnitude of the challenges faced by hemodialysis staff during the pandemic would help to inform interventions during future public health emergencies and could also provide strategies to mitigate stress for dialysis staff and improve care for patients.…”
Section: Introductionmentioning
confidence: 99%